INOVASI BERBASIS MASYARAKAT DESTA (DESA TANGGUH) SEBAGAI UPAYA PENCEGAHAN COVID-19 - Dian Ika Puspitasari; Dian Permatasari, Emdat Suprayitno, Yulia Wardita, Eka Meiri Kurniyati (JOURNAL OF COMMUNITY DEDICATION, 2022)
At the beginning of 2020, Indonesia was shocked by the spread of the Covid-19 virus outbreak. With the spread of the Covid-19 outbreak, millions of people on earth are required to maintain health, hygiene, and comply with several health protocol rules. The public is strongly encouraged to pay attention to the health protocols that have been socialized, such as wearing masks, maintaining distance, and washing hands after activities. The village as the smallest government unit must certainly carry out anticipatory movements in an effort to break the chain of the Corona virus. Community empowerment in preventing Covid-19 must be carried out by involving all components of society by exploring their potential. This is done so that the community can play a role in preventing the spread of Covid-19. With the existence of Tangguh Village, it can also be a means of education for the community to get used to carrying out activities according to health protocols, such as the discipline of wearing masks, getting used to washing hands, and maintaining distance (physical distancing). The public is also expected to be able to better understand the social phenomena surrounding the Corona virus, so that they can anticipate the negative impacts that may occur.